The Image of a Christian Ruler in Baroque Sermons: Wladyslaw Vasa - Vaitkevičiūtė, Viktorija (Senoji Lietuvos literatūra, 2015)
Building on five occasional sermons in Polish dedicated to Wladislaw Vasa (1595–1648), King of Poland and Grand Duke of Lithuania, by Jesuit Jakub Olszewski (1585–1634), Dominican Dominik Krasuski (d. 1655?), and Bernardine Alexander Ostropolski, the paper conveys the image of the ruler dominant in the first half of the seventeenth century, with an emphasis on the Christian aspect.The occasional sermons dedicated to Wladyslaw Vasa promote a panegyric image of an ideal king. He is treated as a state symbol who ensures the country’s security and wellbeing. The power of the ruler is justified by the idea, common throughout centuries, that power rises directly from God because the king is a representative of divine authority. Thus one of the central images pointing to the divine nature of the king is a comparison with Jesus Christ, who was always the point of reference for the rulers. In order to offer as persuasive concept of divinity and eternity of the king as possible, the preachers choose topical images: the ruler is linked to kings Saul and David of the Old Testament, to the prophets, angels, and to the sun.In discussing Wladyslaw’s royal virtues emphasis is laid on his military achievements and his victories: he is described as a brave and wise warrior who took special care of his homeland. Also, as it was usual in the Baroque epoch, the sermons address the Christian values of piety, virtue, and mercy. Thus Wladyslaw as though gives a sense to all possible virtues that in the majority of cases are characteristic of a noble Christian of that time.The analysis of the selected sermons has revealed the still extant theory of two – natural and political – bodies of a king, which points to the continuity, vitality, and eternity of the royal institution and explains why Vivat is always sung to a king. At the same time, the relationship between the ruler and the state is defined in bodily analogies pointing to the ruler’s special linkwith the state and its inhabitants, and presenting an ideal model of state management. The portraits of the ruler in these sermons are special examples for everybody to follow. At the same time, these texts were a good means to consolidate the ruler’s image and the authority of power.
Keywords: -